Uji Kerentanan untuk Insektisida Malathion dan Cypermethrine (Cyf 50 EC) Terhadap Populasi Nyamuk Aedes aegypti di Kota Makassar dan Kabupaten Barru - Sukmawati, Sukmawati; Ishak, Hasanuddin; Arsin, Andi Arsunan (HIGIENE: Jurnal Kesehatan Lingkungan, 2018)
Control of use of chemical insecticides is one way to reduce the vector borne disease dengue hemorrhagic fever (DHF) which are caused by the mosquito Aedes aegypty. This study aims to find out the susceptibility in Makassar City and Barru Regency. The reseach used the quasi experimental method. Female Aedes aegypti mosquitoes that hatch sampled according to the required number as many as 450. The results reveal that in Makassar City, Aedes aegypti mosquitos are tolerant toward malathion 5% insecticide, but they are susceptible to cypermethtine (Cyf 50 EC) 1,5%. In Barru regency, Aedes aegypti mosquitos are still susceptible to malathion 5% insecticide and cypermethrine 1,5% (Cyf 50 EC). There is a difference between the two insecticides in the mortality level based on the contact duration. A comparison of exposure towards the two insecticides shows the values of LT50, LT90, LT95, and LT99. In Makassar City, Malathion 5% insecticides needs more time with the result of 328.87 minutes (5 hours), 1639.06 minutes (27 hours), 2196.94 minutes (37 hours), and 3243.43 minutes (54 hours) respectively; while the results for cypermethrine (Cyf 50 EC) 1.5% are 17.95 minutes, 29.42 minutes, 32.67 minutes, and 38.77 minutes. In Barru regency, the results for malathion 5% insecticide are 25.18 minutes, 55.37 minutes, 63.93 minutes, and 79.99 minutes; while the results for cypertmethrine (Cyf 50 EC) 1.5% are 21.77 minutes, 41.76 minutes, 47.42 minutes, and 58.05 minutes. Keywords : susceptibility testing, malathion, cypermethrine (Cyf 50 EC), Aedes aegypti